d-Xylitol Production from Sugar Beet Press Pulp Hydrolysate with Engineered Aspergillus niger - Melanie Knesebeck; Marcel Rüllke; Veronika Schönrock; J. Philipp Benz; Dirk Weuster-Botz (Microorganisms)
d-Xylitol is a low-calorie and anti-cariogenic sweetener suitable for diabetic patients, making it a valuable ingredient in various health-related applications. In this study, we investigated the production of d-xylitol from l-arabinose derived from sugar beet press pulp (SBPP) hydrolysate using an engineered Aspergillus niger strain. Initial batch studies applying stirred tank bioreactors demonstrated d-xylitol production of 4.6 g L−1 with a yield of 0.37 g d-xylitol g−1 l-arabinose with a synthetic medium. Subsequently, the conversion of enzymatically produced and clarified SBPP hydrolysate was studied. We found that pre-treatment of the enzymatic hydrolysate with activated carbon was essential to remove inhibitory components. Moreover, an automated aeration switch-off was implemented based on the CO2 signal of the off-gas analyzer of the stirred tank bioreactor to prevent d-xylitol degradation after l-arabinose depletion. This resulted in a final d-xylitol concentration of 4.3 g L−1 with an improved yield of 0.43 g d-xylitol g−1 l-arabinose. The feasibility of utilizing the agricultural residue SBPP for d-xylitol production was successfully demonstrated with engineered A. niger.